m^2=n+2,n^2=m+2 (m≠n),求:m^3-2mn=n^3的值.
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 09:33:20
m^2=n+2,n^2=m+2(m≠n),求:m^3-2mn=n^3的值.m^2=n+2,n^2=m+2(m≠n),求:m^3-2mn=n^3的值.m^2=n+2,n^2=m+2(m≠n),求:m^3
m^2=n+2,n^2=m+2 (m≠n),求:m^3-2mn=n^3的值.
m^2=n+2,n^2=m+2 (m≠n),求:m^3-2mn=n^3的值.
m^2=n+2,n^2=m+2 (m≠n),求:m^3-2mn=n^3的值.
“m^3-2mn=n^3”应该是“m^3-2mn+n^3”吧
因为m^2=n+2,n^2=m+2
所以 m^2-n^2=n-m
即 (m-n)(m+n)=-(m-n)
m+n=-1
m^3-2mn+n^3=m·m^2-2mn+n·n^2
=m(n+2)-2mn+n(m+2)
=mn+2m-2mn+mn+2n
=2(m+n)
因为m+n=-1 所以 原式=-2
(m-2n/n-m)-(n/m-n)=
(m-n)^3(n-m)^2(m-n)=_____
(3m-n)(m-2n)=()
(m-n)^2*(m-n)^4=?
(1),(-m-n)(-m+n) (2),(-m+n)(m-n)
(m-2n)(-m-n)
已知3m=2n,则m/(m+n)+n/(m-n)-n^2/(m^2-n^2)=?
已知3m=4n,则m/m+n+n/m-n-m^2/m^2-n^2=
m/n=5/3,求(m/m+n)+(m/m+n)-(n^2/m^2-n^2)
已知m/n=5、,求(m/(m+n))+(m/(m-n))-(n^2/(m^3-n^2))
(m - n)^2 - (m + n)^2(m - n)^2 - (m + n)^2 =
2m+3n+2m+3n+m+2m+3n+n=______
C(m,n)=n(n-1)(n-2)...(n-m+1)/m!中的!
已知|m|=5,|n|=2 |m+n|=m+n,求m-n
(m-2n)(2n+m)-(-3m-4n)(4n-3m)=
已知2(m+n)=1005(m-n),45(m-n)分之180(m+n)=
已知m+n=2012(m-n),则m+n/2(m-n)=?
已知:m*m=n+2,n*n=m+2.求m*m*m-2mn+n*n*n(m不等于n).